Stereoselective synthesis of (-)-galantinic acid - Dubey, Abhishek; Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
An efficient and highly concise synthesis of (-)-galantinic acid has been achieved using an asymmetric allylation reaction of Garner's aldehyde.
Keywords: Amino alcohol; Chiral pool; iterative asymmetric allylation; Oxidation; stereoselective synthesis